2015
DOI: 10.2105/ajph.2015.302638
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Law Enforcement in Overdose Reversal Initiatives: Authorization and Liability for Naloxone Administration

Abstract: Opioid overdose is reversible through the timely administration of naloxone, which has been used by emergency medical services for decades. Law enforcement officers (LEOs) are often the first emergency responders to arrive at an overdose, but they are not typically equipped with naloxone. This is rapidly changing; more than 220 law enforcement agencies in 24 states now carry naloxone. However, rollout in some departments has been hampered by concerns regarding officer and agency liability. We systematically ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 47 publications
0
62
0
Order By: Relevance
“…289 Bystanders who have used drugs may also be reluctant to contact the police or medical emergency personnel for fear of being arrested themselves. 290 …”
Section: Drug Policy and Death From Overdosementioning
confidence: 99%
“…289 Bystanders who have used drugs may also be reluctant to contact the police or medical emergency personnel for fear of being arrested themselves. 290 …”
Section: Drug Policy and Death From Overdosementioning
confidence: 99%
“…Deaths involving opioid pain relievers and heroin increased 200% between 2000 and 2014 (Rudd, 2015). Training and equipping professional first responders (police officers; firefighters; Emergency Medical Technicians or EMTs), who are often the first to arrive at an overdose emergency, has been advocated widely (Office of the Attorney General, 2014; Davis et al, 2014; 2015; Rando et al, 2015; Childs, 2016). Research has consistently demonstrated that training increases overdose-related knowledge and appropriate use and administration of naloxone (Wagner et al, 2016; Saucer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some programmes have additionally factored in around US$10 for staff time per kit (Coffin & Sullivan, 2013). More recently even higher prices have been reported (for example US$60-$80 for a 2 dose rescue kit) (Davis, Carr, Southwell, & Beletsky, 2015), though even at much higher prices naloxone supply to heroin users has been demonstrated to be cost 'What is known about community pharmacy supply of naloxone': A scoping review.…”
mentioning
confidence: 99%